The Influence of Selection, Motivation and Utilization of Information System Academic for Lecturer (SIAD) on the Lecturer Performance - Syafitry Sitorus, Debby; Amelia Putri, Anisa; Rahmat Hidayat, Panca; Rostina, Cut Fitri (Golden Ratio of Human Resource Management, 2021)
Lecturer Academic Information System (SIAD) is an academic service facility that lecturers can use to accommodate and manage teachers' activities, including lectures, assignments, communication, and discussions with students. However, lecturers' obstacles in supporting educational processes include the obstacles of leak of features and items/ service forums in the academic portal /SIAD online. This research aims to find the influence of selecting the system, motivation, and utilization of academic information system lecturers (SIAD) on the performance of lecturers at the Faculty of Economics, University of Prima Indonesia. The study will test the variables both partially and simultaneously. Samples were taken from lecturers recorded in the management study program of 60 people. The test result obtained a calculated value of F (17,866) > F table (2.76) and a probability of significance of 0.000 < 0.05, it was concluded that simultaneously H0 was rejected, which means the selection, motivation, and utilization of SIAD had a positive and significant effect on the performance of lecturers at the Faculty of Economics, Universitas Prima Indonesia Medan. The result of the calculation of the coefficient of determination obtained an adjusted R Square value of 0.462.